Treatment of Iron deficiency anemia induces weight loss and improves metabolic parameters - GÜLALİ AKTAŞ; aytekin Alcelik; Abdullah Yalcin; Sevim Karacay; Sule Kurt; Merve Akduman; Haluk Savli (Mediterranean Journal of Hematology and Infectious Diseases)
Aims: The treatment of iron deficiency anemia is oral iron replacement which has side effects mostly related with gastrointestinal system. A significant rate of the patients that discontinuing the treatment complained of weight gain during treatment in our clinical practise, despite, oral iron preparations known to have such a side effect in adults. Therefore, we planned to investigate this myth whether iron preparations cause an increase in weight, waist circumference, body mass index and laboratory metabolic parameters that may accompany to weight gain.